Good Night, Indiana University - Salinas, Joey B. Lax (Book collections on Project MUSE., 2023)
"Good Night, Indiana University takes a whimsical journey through IU's Bloomington campus as the sun is slowly setting. The perfect bedtime book for IU alums and their little ones, Good Night, Indiana University whispers good night and sweet dreams to beloved campus landmarks such as Sample Gates, Dunn's Woods, and Memorial Stadium. For Hoosiers of all ages, Good Night, Indiana University is sure to become a cherished family favorite. So "Good night cream and crimson, under the light of a crescent moon. Good Night Indiana University, in my dreams I'll see you soon.""--